2011
DOI: 10.1158/0008-5472.can-11-0027
|View full text |Cite
|
Sign up to set email alerts
|

Human Neural Stem Cell Transplantation Ameliorates Radiation-Induced Cognitive Dysfunction

Abstract: Cranial radiotherapy induces progressive and debilitating declines in cognition that may, in part, be caused by the depletion of neural stem cells. The potential of using stem cell replacement as a strategy to combat radiation-induced cognitive decline was addressed by irradiating athymic nude rats followed 2 days later by intrahippocampal transplantation with human neural stem cells (hNSC). Measures of cognitive performance, hNSC survival, and phenotypic fate were assessed at 1 and 4 months after irradiation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
159
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 113 publications
(165 citation statements)
references
References 42 publications
5
159
1
Order By: Relevance
“…The initial acquisition of the conditioned freezing response was not impacted in any of the cohorts (similar posttraining), nor was amygdala function (similar cue test) (20). These data indicate that radiation-induced deficits in hippocampal function could be ameliorated using MV and were functionally equivalent to hNSCs used under similar conditions in many of our past studies (4,8).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…The initial acquisition of the conditioned freezing response was not impacted in any of the cohorts (similar posttraining), nor was amygdala function (similar cue test) (20). These data indicate that radiation-induced deficits in hippocampal function could be ameliorated using MV and were functionally equivalent to hNSCs used under similar conditions in many of our past studies (4,8).…”
Section: Discussionsupporting
confidence: 54%
“…Despite the recognition and prevalence of these adverse side effects, relatively few, if any, long-term satisfactory solutions exist for this unmet medical need. Past work from our laboratory has optimized transplantation parameters and established many of the long-term benefits of human stem cell-based therapies for the treatment of radiationinduced cognitive dysfunction (3)(4)(5). Cranially grafted stem cells have been shown to impart persistent improvements in behavioral performance in irradiated rats over extended postirradiation intervals (1-8 mo) using short-and long-term cognitive testing paradigms (4,6,7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Past data in the same mouse background (i.e., C57Bl6) has found irradiation to elicit cognitive decrements, albeit at longer postirradiation intervals (9,10), and data from us and others using different strains of rat have shown irradiation to elicit hippocampal deficits in learning and memory (8,40,41). Recent data from us has also shown that lowdose irradiation of the same transgenic mouse strain with charged particles elicits decrements in cognition using a novel object recognition test (42).…”
Section: Discussionmentioning
confidence: 85%